2021
DOI: 10.3389/fpsyg.2021.665144
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Feedback Types on Learning With Mobile Quiz Apps

Abstract: Testing is an effective learning method, and it is the basis of mobile quiz apps. Quiz apps have the potential to facilitate remote and self-regulated learning. In this context, automatized feedback plays a crucial role. In two experimental studies, we examined the effects of two feedback types of quiz apps on performance, namely, the standard corrective feedback of quiz apps and a feedback that incorporates additional information related to the correct response option. We realized a controlled lab setting (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
2
4
0
Order By: Relevance
“…This research finding is consistent with Rüth et al ( 2021 ), who found that testing and quizzes were more effective for learning than was repeated exposure to learning materials. Writing practice provides relevant cognitive load, that is, knowledge construction processes that unavoidably lead to learning (Sweller et al, 1998 ; Nückles et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…This research finding is consistent with Rüth et al ( 2021 ), who found that testing and quizzes were more effective for learning than was repeated exposure to learning materials. Writing practice provides relevant cognitive load, that is, knowledge construction processes that unavoidably lead to learning (Sweller et al, 1998 ; Nückles et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…From a students’ perspective, remote learning might be accompanied by a variety of advantages and disadvantages, compared to well-known face-to-face learning environments. For example, remote learning is connected to an increased flexibility in time management and the reception of course material ( Daymont et al, 2011 ), and it may also foster self-regulated learning (e.g., Rüth et al, 2021 ). Also, remote learning may increase the quantity and quality of teaching and learning materials ( Lin et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…(Interviewee 1) I also feel that I need to practice my composition, I do feel that I don't have much practice now. (Interviewee 2) This research finding is consistent with Rüth et al (2021), who found that testing and quizzes were more effective for learning than was repeated exposure to learning materials. Writing practice provides relevant cognitive load, that is, knowledge construction processes that unavoidably lead to learning (Sweller et al, 1998;Nückles et al, 2020).…”
Section: Writing Peformancesupporting
confidence: 75%